Genomic and Phenotypic Analyses Reveal Mechanisms Underlying Homing Ability in Pigeon. (10th September 2019) - Shao, Yong; Tian, Hang-Yu; Zhang, Jing-Jing; Kharrati-Koopaee, Hamed; Guo, Xing; Zhuang, Xiao-Lin; Li, Ming-Li; Nanaie, Hojat Asadollahpour; Dehghani Tafti, Elahe; Shojaei, Bahador; Reza Namavar, Mohammad; Sotoudeh, Narges; et al.
Abstract: The homing pigeon was selectively bred from the domestic pigeon for a homing ability over long distances, a very fascinating but complex behavioral trait. Here, we generate a total of 95 whole genomes from diverse pigeon breeds. Comparing the genomes from the homing pigeon population with those from other breeds identifies candidate positively selected genes, including many genes involved in the central nervous system, particularly spatial learning and memory such as LRP8 . Expression profiling reveals many neuronal genes displaying differential expression in the hippocampus, which is the key organ for memory and navigation and exhibits significantly larger size in the homing pigeon. In addition, we uncover a candidate gene GSR (encoding glutathione-disulfide reductase) experiencing positive selection in the homing pigeon. Expression profiling finds that GSR is highly expressed in the wattle and visual pigment cell layer, and displays increased expression levels in the homing pigeon. In vitro, a magnetic field stimulates increases in calcium ion concentration in cells expressing pigeon GSR . These findings support the importance of the hippocampus (functioning in spatial memory and navigation) for homing ability, and the potential involvement of GSR in pigeon magnetoreception.